2010
DOI: 10.1161/strokeaha.109.559724
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intravenous Thrombolysis for Acute Ischemic Stroke in Patients Receiving Antiplatelet Therapy at Stroke Onset

Abstract: Background and Purpose-Antiplatelets (APs) may increase the risk of symptomatic intracerebral hemorrhage (ICH) following intravenous thrombolysis after ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 24 publications
7
75
3
2
Order By: Relevance
“…First, in one of the largest studies in this meta‐analysis (Xian et al29), patient functional status was not evaluated on day 90, which is generally recognized as the most appropriate time point for final functional outcome assessment after acute ischemic stroke 39. It can be observed that there existed a significant discrepancy between the findings of this study and the results of the other largest study18 that measured functional outcomes on day 90 (OR 1.16, 95% CI 1.09–1.24 versus OR 1.02, 95% CI 0.97–1.08), which suggested that the impact of prestroke antiplatelet therapy on functional outcomes after thrombolysis might possibly be time dependent. Second, there were obvious differences in the odds of sICH and favorable outcome among patients receiving different prestroke antiplatelet medications.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…First, in one of the largest studies in this meta‐analysis (Xian et al29), patient functional status was not evaluated on day 90, which is generally recognized as the most appropriate time point for final functional outcome assessment after acute ischemic stroke 39. It can be observed that there existed a significant discrepancy between the findings of this study and the results of the other largest study18 that measured functional outcomes on day 90 (OR 1.16, 95% CI 1.09–1.24 versus OR 1.02, 95% CI 0.97–1.08), which suggested that the impact of prestroke antiplatelet therapy on functional outcomes after thrombolysis might possibly be time dependent. Second, there were obvious differences in the odds of sICH and favorable outcome among patients receiving different prestroke antiplatelet medications.…”
Section: Discussionmentioning
confidence: 75%
“…For the 2 pairs of studies that analyzed overlapped data from the same registries, we included the latest and those with the largest samples for meta‐analysis 14, 18, 22, 26. The detailed selection process is summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 However, they found no significant increase in the risk for mortality or poor functional outcome, irrespective of the Anti-platelet subgroup or Symptomatic intracranial hemorrhage definition. This analysis concluded that the absolute excess of Symptomatic intracranial hemorrhage of 1.4% (2.1%) in the pooled Anti-platelet group is small compared with the benefit of thrombolysis seen in randomized trials.…”
mentioning
confidence: 91%